Tecendo a política. Itinerários de participação política de mulheres em movimentos sociais contemporâneos na Argentina - Bogado, Adriana Marcela (2009)
This thesis is dedicated to the study of women‟s political participation in contemporary social movements in Argentina, by the means of the reconstruction of their course of life, from the perspective of their experiences and memories. In a context of crisis, as consequence of the neoliberal model implemented, the social movements present themselves as key areas of political struggle and, at the same time, as spaces of construction of cultural, social, political and economic alternatives. In relation with these organizations, the paths of political participation are developed and/or enhanced, however, we identify a process in which women participation becomes invisible. In this research we analyzed the mentioned participation with the aim to understand the factors and practices that generate exclusion and that which encourages its development, identifying the existence of limits and the different possibilities for women‟s political activities. We also situated the political participation within the theoretical and methodological universe of empowerment and gender relationships, in order to contribute to understand women‟s situation in the current social, political, economic and cultural panorama. The field work was developed with participants and leaders of Movimiento de Mujeres en Lucha (MML), in General Roca (Río Negro) and Rosario (Santa Fe); and with participants and leaders of the first pickets in the rural areas of Argentina and in the state of Buenos Aires, the Corriente Clasista Combativa (CCC, Zona Norte). Using the methodology of Oral History and the Participant Observation we rebuild the course of life of six women, presented in the form of biographical portraits (portraits). Each one of the portraits describes the processes of political engagement, the current involvement and future prospects, pointing out the connections with family, social and professional dimensions. Although feeling "forced" to leave in order to fight, these women have found recognition in the struggle. They also strengthened their networks of sociability, found courage to draw their own process of empowerment and they are still learning about politics in the dialectic of their course of life.